Study of Ventilator Associated Pneumonia in NICU at Tertiary Care Centre - Edward, C.; Osman, H. (Asian Journal of Clinical Pediatrics and Neonatology, 2017)
Background: Ventilator associated pneumonia (VAP) is a common nosocomial infection which occurs in 9% to 27% of mechanically ventilated patients. It is an important cause of morbidity in ventilated patients increasing their ventilator days, increased length of stay in intensive care unit (ICU) and hospital as well as increased cost burden on patient and or family. Methods: This study conducted ina tertiary care centre. It is an observational prospective study. Results: Total 50 neonates who were ventilated more than 48 hours during this period were included in this study. From the 50 neonates nine (18%) neonates were associated with pneumonia. Organisms which isolated from the tracheal secretion were 11.1% Acinobacter, 33.4% Staphylococcus, 33.4% Klebsiella, 11.1% E. coli, 11.1% Pseudomonas. Most common organism responsible for mortality is Klebsiella (50%) & Staphylococcus (20%). Conclusion: This study conclude that The pathogenesis of VAP involves the micro-aspiration of oropharyngeal and/or gastric secretions that have been contaminated/colonized with pathogenic organisms. Efforts to prevent VAP are focused on early extubating and preventing aspiration. Early diagnosis and treatment help limit VAP related morbidity and mortality.